Diet and Dental Caries: The Pivotal Role of Free Sugars Reemphasized. (October 2015) - Sheiham, A.; James, W.P.T.
The importance of sugars as a cause of caries is underemphasized and not prominent in preventive strategies. This is despite overwhelming evidence of its unique role in causing a worldwide caries epidemic. Why this neglect? One reason is that researchers mistakenly consider caries to be a multifactorial disease; they also concentrate mainly on mitigating factors, particularly fluoride. However, this is to misunderstand that the only cause of caries is dietary sugars. These provide a substrate for cariogenic oral bacteria to flourish and to generate enamel-demineralizing acids. Modifying factors such as fluoride and dental hygiene would not be needed if we tackled the single cause—sugars. In this article, we demonstrate the sensitivity of cariogenesis to even very low sugars intakes. Quantitative analyses show a log-linear dose-response relationship between the sucrose or its monosaccharide intakes and the progressive lifelong development of caries. This results in a substantial dental health burden throughout life. Processed starches have cariogenic potential when accompanying sucrose, but human studies do not provide unequivocal data of their cariogenicity. The long-standing failure to identify the need for drastic national reductions in sugars intakes reflects scientific confusion partly induced by pressure from major industrial sugar interests.